High Altitude Balloon Payload Design for Atmospheric Observations - Wiyagi, Rama Okta; Danardono, .; Agus, Try Ahmad (Universitas Muhammadiyah Yogyakarta, 2017)
In 2016, Microcontroller Research Group at Dept. of Electrical Engineering Universitas Muhammadiyah Yogykarta has designed and developed a payload for High Altitude Balloon. This payload has function measuring atmospheric parameter vertically and sending the data to ground station on earth using telemetry. The parameters measured are air pressure, temperature and relative humidity. Besides sending these parameters, payload also have mission monitoring real positions of payload using GPS, real time video transmission,regulary capturing and sending image from payload . This payload is tested on the annual Atmosphere Balloon Payload Competition (KOMBAT) 2016. This paper will describe the design payload, payload software algorithms and the results that have been obtained.Â